2011
DOI: 10.1007/s11011-011-9253-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of respiratory chain activity in lymphocytes of patients with Alzheimer disease

Abstract: Alzheimer disease (AD) is a progressive neurodegenerative disease associated with cognitive impairment in multiple domains, such as memory and executive functions. Studies reveal damage in the electron transport chain of patients with AD, suggesting that this mitochondrial dysfunction plays an important role in the pathophysiology of the disease. Blood samples were taken from patients with AD (n = 20) and older subjects without dementia (n = 40) to evaluate the activity of complexes I, II, II-III, and IV of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…ETC activities of human lymphocytes were evaluated in AD patients, and increased complexes II and IV activities were observed; this might be a compensatory mechanism to supply the energy [74]. Evidences of ETC dysfunctions in AD are summarized in Table 1.…”
Section: Impairment Of Etc In Admentioning
confidence: 99%
“…ETC activities of human lymphocytes were evaluated in AD patients, and increased complexes II and IV activities were observed; this might be a compensatory mechanism to supply the energy [74]. Evidences of ETC dysfunctions in AD are summarized in Table 1.…”
Section: Impairment Of Etc In Admentioning
confidence: 99%
“…Additionally, the prevalence of AD increases exponentially with age in people 65 or older (Hansson et al, 2006). The disease is symptomatically characterized by progressive memory deficits, cognitive impairments, and personality changes, which can be attributed to deteriorating synaptic function and the subsequent loss of neurons in vulnerable regions of the brain, including the neocortex, the limbic system, and the subcortical regions (Fassbender et al, 2001). From a histopathological view, AD is characterized by senile plaques and neurofibrillary tangles (NFT) in the medial temporal lobe and cortical areas of the brain (Hansson et al, 2006).…”
Section: Alzheimer’s Disease – Unlimited Cost But Limited Remedymentioning
confidence: 99%
“…Some studies have found no effect of AD status on lymphocyte mitochondrial activity (Molina et al, 1997), whereas a recent study showed increased activity of mitochondrial respiratory chain complexes II and IV in lymphocytes isolated from patients with AD when compared with controls (Feldhaus et al, 2011). Another study showed that although there was no baseline difference in lymphocyte mitochondrial enzyme activities between controls and AD patients, those patients who were treated with the cholinesterase inhibitor rivastigmine showed increased activity of complexes II, III, and IV, indicating that increased mitochondrial efficiency might be associated with better disease outcome.…”
Section: Clinical Implications For Biomarker Identification and Thmentioning
confidence: 99%